(untitled) (Bulletin of criminological association of Ukraine, 2024)
The scientific research is aimed at highlighting the theoretical and legal issues of a civil plaintiff’s and a civil defendant’s representative participation in criminal proceedings. The emphasis is placed on the peculiarity of legislative regulation of filing a civil lawsuit in criminal proceedings, namely, partial regulation of this procedure by the rules of civil procedure legislation and similarity of the legal relations subject matter. This situation prompts a comparative analysis of the civil and criminal procedural laws in terms of participation of a representative of a civil plaintiff and defendant. It has been established that criminal procedural legislation, as compared to civil procedural legislation, significantly narrows the list of persons who may be representatives of a civil plaintiff and a defendant. It is proposed to expand the list of persons who may be representatives of a civil plaintiff and defendant.